Strategy for Enhancing the Performance of Marine and Fisheries Resources Surveillance (Case Study at the Marine and Fisheries Resources Surveillance Base in Tual) (Torani Journal of Fisheries and Marine Science, 2024)
This study aims to formulate strategies to enhance the performance of marine and fisheries resource surveillance at the Marine and Fisheries Resources Surveillance Base (PSDKP) in Tual. The effectiveness of surveillance is a key factor in preserving resources and preventing illegal activities that harm the state. This research employs two main analytical approaches, the Analytic Hierarchy Process (AHP) and SWOT analysis, to identify and prioritize the most relevant strategies. The AHP results indicate that human resources (HR) have the highest weight (0.657), followed by infrastructure and surveillance systems (0.259), and policy (0.084). Based on the SWOT analysis, the prioritized strategies include enhancing HR capacity with a weight of 0.571, developing surveillance systems with a weight of 0.191, strengthening cooperation with a weight of 0.123, and advocating for policy and lobbying with a weight of 0.114. The implementation of these strategies is expected to improve surveillance effectiveness, reduce violations, and support the sustainability of marine and fisheries resources in the PSDKP Tual area.